International Orthopaedic Volunteer Opportunities in Low and Middle-Income Countries. (18th May 2022) - Miclau, Theodore; MacKechnie, Madeline C.; Born, Christopher T.; MacKechnie, Michael A.; Dyer, George S.M.; Yuan, Brandon J.; Dawson, John; Lee, Cassandra; Ishmael, Chad R.; Schreiber, Verena M.; Tejwani, Nirmal C.; Ulmer, Todd; et al.
Abstract: Globally, the burden of musculoskeletal conditions continues to rise, disproportionately affecting low and middle-income countries (LMICs). The ability to meet these orthopaedic surgical care demands remains a challenge. To help address these issues, many orthopaedic surgeons seek opportunities to provide humanitarian assistance to the populations in need. While many global orthopaedic initiatives are well-intentioned and can offer short-term benefits to the local communities, it is essential to emphasize training and the integration of local surgeon-leaders. The commitment to developing educational and investigative capacity, as well as fostering sustainable, mutually beneficial partnerships in low-resource settings, is critical. To this end, global health organizations, such as the Consortium of Orthopaedic Academic Traumatologists (COACT), work to promote and ensure the lasting sustainability of musculoskeletal trauma care worldwide. This article describes global orthopaedic efforts that can effectively address musculoskeletal care through an examination of 5 domains: clinical care, clinical research, surgical education, disaster response, and advocacy.